Interactive effects of drought and high night temperature on physiology and yield components of cowpea (Vigna unguiculata (L.) Walp.) - Alekhya Chakravaram; Lekshmy V. Sankarapillai; Sujan Poudel; Raju Bheemanahalli (Journal of Agriculture and Food Research)
Cowpea is a nutrient-rich vegetable legume with significant potential to address protein-calorie malnutrition. However, exposure to drought stress (DS) and high night temperature (HNT) substantially threaten crop production, including cowpea. Several studies have examined the effects of DS, but there is limited information on the combined impact of DS and HNT during the reproductive growth stage of cowpeas. This study quantified the effects of individual DS or HNT and combination on physiological and yield-related traits. At the reproductive stage, three genetically diverse cowpea genotypes were subjected to four distinct growing conditions: (i) control (CNT, 24 °C night temperature, full irrigation), (ii) DS (24 °C night temperature, 40 % irrigation of CNT), (iii) HNT (28 °C night temperature, full irrigation), and (iv) DS + HNT (28 °C night temperature + 40 % irrigation of CNT). All treatments maintained a common daytime temperature of 32 °C. A 3.2 °C nighttime rise under DS reduced stomatal conductance (91.5 %), photosystem efficiency (17.4 %), resulting in lower pod weight (64.5 %), seeds per pod (14 %), and seed count (66 %). Individual stressors notably impacted seed number and yield, with DS resulting in reductions exceeding 30 %, followed by HNT at 23 % compared to CNT. Overall, seed yield decreased by 63 % and seed protein by 25.1 % under DS + HNT. Among genotypes, EpicSelect.4 showed greater tolerance to DS for physiology parameters, while UCR 369 performed better under HNT for yield. The stress impact on cowpea performance ranked as DS + HNT > DS > HNT, highlighting the need for further research to understand molecular mechanisms that cause different stress responses during reproductive and grain-filling phases.